Analysis of Maqsud tahqiqi al-adl in Multi-Level Marketing transactions from Ibn Taimiyyah's perspective - Kamaluddin, Imam; Nurafni, Fina (DAS Institute, 2025)
This study aims to analyze the extent of the application of maqsud tahqiqi al-'adl in multi-level marketing (MLM) transactions. This is very important to do a review by analyzing more deeply from the aspect of the halal system, model, and products traded. That is because people consider MLM transactions very promising to get large profits through relatively small capital. However, DSN-MUI has issued fatwa No. 75/DSN MUI/VII 2009: 75/DSN MUI/VII 2009 on the halalness of Sharia Multi-Level Marketing (MLMS). But in practice, there is still a money game in giving bonuses that do not meet sharia principles. This research is library research using qualitative methods sourced from secondary data obtained by collecting information from various kinds of literature. The analysis technique used in this research is descriptive-analytical. This research seeks to provide a comprehensive and in-depth understanding of the MLM business and is analyzed with maqasid sharia Ibn Taymiyyah. The results showed that sharia MLM is a legitimate transaction because it does not contradict the arguments and is by the sale and purchase contract if practiced by the conditions in DSN Fatwa No. 75/dsn mui/vi: 75/DSN MUI/VII 2009. The system adopted by MLMS in the way of donation is by one of Ibn Taymiyyah's maqasid, namely Maqsud tahqiqi al-adl, which states